Clinical outcomes and response to treatment of patients receiving topical treatments for pyoderma gangrenosum: a prospective cohort study - Thomas, Kim S.; Ormerod, Anthony D.; Craig, Fiona E.; Greenlaw, Nicola; Norrie, John; Mitchell, Eleanor; Mason, James M.; Johnston, Graham A.; Wahie, Shyamal; Williams, Hywel C. (Elsevier, 2016)
Background: pyoderma gangrenosum (PG) is an uncommon dermatosis with a limited evidence base for treatment.